Tomographic evaluation of the glands and lymph nodes of the cervical region in the crab-eating fox (Cerdocyon thous) - da Costa, Isis Pinto [UNESP]; Schimming, Bruno Cesar [UNESP]; de Oliveira, Fernanda Gabriela [UNESP]; da Silva, Jeana Pereira [UNESP]; de Melo Santos, Mariana [UNESP]; de Lima, Heloisa Coppini [UNESP]; Castañeda, Brayan Sayed López [UNESP]; da Silva, Suelen Lorena [UNESP]; Tsunemi, Miriam Harumi [UNESP]; Mamprim, Maria Jaqueline [UNESP] (Wiley, 2024)
The present study aimed to determine references of normality of computed tomographic (CT) images of mandibular and parotid salivary glands (PSGs), medial retropharyngeal and mandibular lymph nodes and thyroid gland of 10 clinically healthy crab-eating foxes, Cerdocyon thous. The location, shape, homogeneity of the parenchyma, and length, height, width and pre- and post-contrast attenuation values were evaluated. The anatomical structures in the crab-eating foxes studied here presented anatomical landmarks similar to those described for domestic dogs, and showed a regular shape and homogenous parenchyma, except for the PSGs, that showed predominantly heterogeneous parenchyma. The thyroid gland topography in the crab-eating fox, though very similar, is not identical to the domestic dog and the presence of isthmus between the lobes was not detected. The values obtained from crab-eating foxes are within the normal range, although in the upper limits of dogs. There was a significant difference in the attenuation values between the right and left lobes of the thyroid gland, being greater in the left thyroid lobe. CT attenuation values ranges for this neotropical canid can be incorporated into routine staging procedures in the veterinary care of the crab-eating foxes. Furthermore, the CT images obtained were similar to those of healthy dogs, and the information obtained can be considered as initial tomographic references of normality in the cervical structures of the crab-eating fox, in order to aid in the diagnosis of future diseases that can affect this neotropical canid.
Keywords: crab-eating fox; diagnostic imaging; lymph nodes; neck; salivary glands; thyroid gland